Research of Changing the Driver's Reaction Time in the Traffic Jam - Gyulyev, Nizami; Lobashov, Oleksii; Prasolenko, Oleksii; Burko, Dmytro (International Journal of Engineering and Technology, 2018)
In this research the main attention is paid to establishing dynamics of changes in the driver’s reaction time in a traffic jam that affects traffic safety.With the help of the regression model, graphs of driver’s reaction time are constructed taking into account different age groups and types of the nervous system depending on the initial level of fatigue at the entrance to traffic jam and duration of traffic jam.Analysis of these graphs allowed us to establish trends in the driver’s reaction time in traffic jams, which indicate an increase in the driver’s reaction time with an increase in the time spent in the traffic jam. However, at the beginning of the traffic jam, depending on the initial fatigue level, different combinations of the reaction time change occur at the entrance to the traffic jam: at low values, the reaction time increases, and at high values it decreases. It was also found that the traffic jam has a different effect on the reaction time of drivers depending on their temperament. For the reaction time of the driver-phlegmatic traffic jam does not have a significant impact.